Current and potential future biological uses of Saussurea costus (Falc.) Lipsch: A comprehensive review - Elnour, Ahmed A.M.; Abdurahman, Nour Hamid (Elsevier Ltd, 2024)
Background: Saussurea costus (S. costus) is a critically endangered medicinal plant that has been extensively studied for its chemical composition, significance, and therapeutic potential as traditional phytomedicine. This comprehensive review aims to provide a thorough understanding of S. costus, including its biological activities, chemical makeup, and potential therapeutic uses in biotechnology. Objectives: This study investigated the pharmacological properties of S. costus, including its antimicrobial, antioxidant, and antifungal properties, and its usefulness in treating conditions such as thyroid disorders and liver injury. This study also aimed to assess and improve the techniques used to extract bioactive compounds and to develop effective methods for harvesting these compounds from medicinal plants. Methods: This review analyzed the available literature on the phytochemical makeup and bioactivity of S. costus extract using techniques such as molecular docking against SARS-CoV-2 protease, green extraction methods, and phytochemical analysis. Results: This review revealed that S. costus possesses various pharmacological properties, including antimicrobial, antiviral, anti-inflammatory, and anticancer activities. It is effective in combating fungal infections, reducing inflammation, treating cancer, and inhibiting viral replication, and has the potential to control Candida species. Moreover, S. costus has been explored for its capacity to synthesize nanoparticles with antimicrobial properties and for its potential in treating thyroid disorders and liver injury. Recommendations: Despite promising results, additional research is necessary to fully comprehend the benefits of S. costus and validate its effectiveness in clinical settings. Future research should focus on standardized methodologies and rigorous clinical trials to confirm the safety and effectiveness of S. costus in various medical fields as well as further investigate its biotechnological and pharmaceutical applications.